"This Broadcast Is Being Watched Live by Millions of Americans": Vague Language in Jimmy Kimmel's Oscars 2017 Opening Monologue - Wahyuningsih Wahyuningsih; Nina Setyaningsih (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2018)
When delivering a speech or talk, a speaker shares a great deal of background knowledge to the audience. However, as human being, the speaker often gets nervous and forgets the words to say. Sometimes the speaker is not able to memorize all information that s/he wants to present to the audience. In fact, during the talk, the speaker must speak fluently to maintain a good situation and communication to the audience. Therefore, to fill a gap during a talk because the speaker could not memorize every detail of information to be presented, using vague language sometimes becomes an option. Vague language may also be used for other purposes besides nervousness and memory problem, i.e. as a tension management (Trappes-Lomax, 2007). This research explores vague language as tension management device used by Jimmy Kimmel as the host in the Oscars opening monologue in 2017. The method used in this research was qualitative descriptive since it describes the data in the form of word or sentence. The results demonstrate that Jimmy Kimmel used vague language types such as conventional indirectness, category and quantity approximation, hedges, modal expressions, implicitness, euphemisms, softeners and down toners as tension management devices. Furthermore, vague language can function as hedges for Jimmy Kimmel’s statements when the information he presented is not precise.